Overview of the Morphology and Chemistry of Diagenetic Features in the Clay‐Rich Glen Torridon Unit of Gale Crater, Mars. Issue 12 (23rd December 2022) - Gasda, Patrick J.; Comellas, Jade; Essunfeld, Ari; Das, Debarati; Bryk, Alexander B.; Dehouck, Erwin; Schwenzer, Susanne P.; Crossey, Laura; Herkenhoff, Kenneth; Johnson, Jeffrey R.; Newsom, Horton; Lanza, Nina L.; et al.
Abstract: The clay‐rich Glen Torridon region of Gale crater, Mars, was explored between sols 2300 and 3007. Here, we analyzed the diagenetic features observed by Curiosity, including veins, cements, nodules, and nodular bedrock, using the ChemCam, Mastcam, and Mars Hand Lens Imager instruments. We discovered many diagenetic features in Glen Torridon, including dark‐toned iron‐ and manganese‐rich veins, magnesium‐ and fluorine‐rich linear features, Ca‐sulfate cemented bedrock, manganese‐rich nodules, and iron‐rich strata. We have characterized the chemistry and morphology of these features, which are most widespread in the higher stratigraphic members in Glen Torridon, and exhibit a wide range of chemistries. These discoveries are strong evidence for multiple generations of fluids from multiple chemical endmembers that likely underwent redox reactions to form some of these features. In a few cases, we may be able to use mineralogy and chemistry to constrain formation conditions of the diagenetic features. For example, the dark‐toned veins likely formed in warmer, highly alkaline, and highly reducing conditions, while manganese‐rich nodules likely formed in oxidizing and circumneutral conditions. We also hypothesize that an initial enrichment of soluble elements, including fluorine, occurred during hydrothermal alteration early in Gale crater history to account for elemental enrichment in nodules and veins. The presence of redox‐active elements, including Fe and Mn, and elements required for life, including P and S, in these fluids is strong evidence for habitability of Gale crater groundwater. Hydrothermal alteration also has interesting implications for prebiotic chemistry during the earliest stages of the crater's evolution and early Mars. Plain Language Summary: The NASA Curiosity rover explored the ancient lakebed rocks within the Glen Torridon region of Mars from January 2019 to January 2021. The rover observed many signs that the bedrock was changed by groundwater, especially in the higher elevations along the rover's path. We used data from the rover's ChemCam instrument to record chemistry, and images from four cameras on the rover to look for physical changes to the rocks. When the rock in Glen Torridon was altered by groundwater, it introduced a variety of physical and chemical changes to the rock, and the amount of some elements (sodium, calcium, iron, magnesium, or manganese) increased in the rocks in association with these physical changes to the rocks. We can use these changes in the rock's characteristics to determine the type of water that changed these rocks on Mars (its chemical composition, its temperature, acidic vs. basic, oxidizing vs. reducing) at the time that the changes occurred. We found that many types of groundwater mixed at different times to cause changes to the rocks. At least one of the groundwater types was warmer than what was previously expected and could be related to the impact that formed the crater. Key Points: Glen Torridon in Gale crater underwent multiple generations of diagenesis of the bedrock that widely varies in chemistry and morphology One hypothesis suggests an initial enrichment of elements occurred during the Gale's post‐impact hydrothermal alteration phase of evolution We estimate that at least one type of vein in Glen Torridon required warm temperatures, and highly reducing and alkaline fluid to form